2021
DOI: 10.1111/gbi.12459
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic controls on the microbial habitability of Mars‐analogue hydrothermal environments

Abstract: Due to their potential to support chemolithotrophic life, relic hydrothermal systems on Mars are a key target for astrobiological exploration. We analysed water and sediments at six geothermal pools from the rhyolitic Kerlingarfjöll and basaltic Kverkfjöll volcanoes in Iceland, to investigate the localised controls on the habitability of these systems in terms of microbial community function. Our results show that host lithology plays a minor role in pool geochemistry and authigenic mineralogy, with the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…Mixing of the two distinct water sources could promote biological activity by introducing chemical disequilibrium that could fuel chemotrophic microbial metabolisms. Previous studies of a volcanic subglacial lake and glacially influenced volcanic lakes have found molecular evidence for chemotrophic bacteria that utilize the redox gradient between geothermal and glacial water sources by using iron, sulfide, sulfur, or hydrogen (common geothermal components) as electron donors and oxygen, sulfate, nitrate, or carbon dioxide (common glacier components) as electron acceptors (Gaidos et al., 2009; Moreras‐Marti et al., 2021). The glacier discharge we sampled was cold (0.7°C) and contained a relative abundance of compounds that are common in oxidized waters (e.g., NO 3 − and O 2 ) but few compounds that are common in reduced waters (e.g., sFe and sMn) while the opposite was observed in the warm (51.5°C) hot spring discharge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mixing of the two distinct water sources could promote biological activity by introducing chemical disequilibrium that could fuel chemotrophic microbial metabolisms. Previous studies of a volcanic subglacial lake and glacially influenced volcanic lakes have found molecular evidence for chemotrophic bacteria that utilize the redox gradient between geothermal and glacial water sources by using iron, sulfide, sulfur, or hydrogen (common geothermal components) as electron donors and oxygen, sulfate, nitrate, or carbon dioxide (common glacier components) as electron acceptors (Gaidos et al., 2009; Moreras‐Marti et al., 2021). The glacier discharge we sampled was cold (0.7°C) and contained a relative abundance of compounds that are common in oxidized waters (e.g., NO 3 − and O 2 ) but few compounds that are common in reduced waters (e.g., sFe and sMn) while the opposite was observed in the warm (51.5°C) hot spring discharge.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the microbes detected in a subglacial volcanic crater lake system in Iceland were related to microbes capable of using sulfide, sulfur, or hydrogen (common geothermal components) as electron donors and oxygen, sulfate, or carbon dioxide (common glacier components) as electron acceptors (Gaidos et al, 2009). Since the mixing of geothermal waters and glacier meltwater can provide life's basic requirements, such environments are high priority targets in the search for extraterrestrial life (Garcia-Lopez & Cid, 2017;Schulze-Makuch et al, 2007) and have been studied in analog research on Earth (Gaidos et al, 2004(Gaidos et al, , 2009Moreras-Marti et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surface hydrothermal features (e.g., hot springs, mudpots, geyser and fumaroles) have also been investigated to evaluate the composition and geochemical influences on their microbial communities, including in the Taupo Volcanic Zone of New Zealand (Power et al, 2018), the Tengchong Volcanic Field of China (Hou et al, 2013), YNP (Colman et al, 2019; Inskeep et al, 2013; Mitchell, 2009), and Iceland (Castenholz, 1969a; Moreras‐Marti et al, 2021), among others. Overall, a growing consensus is that pH and, to a lesser extent, temperature primarily explain the distributions of microbial taxa within geothermal systems, regardless of which hydrothermal system is being considered (Boyd et al, 2010; Colman et al, 2019; Inskeep et al, 2013; Mitchell, 2009; Moreras‐Marti et al, 2021; Power et al, 2018). Nevertheless, few studies have evaluated the associations of geochemistry with microbial community compositions across hydrothermal systems that exhibit differing tectonic, geological and hydrologic settings.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed that hot springs support microbial communities that are exceptionally diverse and vary in their response to physical and geochemical parameters ( Inskeep et al, 2013 ; Sharp et al, 2014 ; Lindsay et al, 2018 ; Power et al, 2018 ; Colman et al, 2019a , b ; Podar et al, 2020 ). Some studies have found pH to be the primary physical parameter that influences the microbial community composition of hot springs in Yellowstone National Park ( Boyd et al, 2010 ; Inskeep et al, 2013 ; Colman et al, 2016 , 2019a , b ), Tengchong, China ( Hou et al, 2013 ; Xie et al, 2015 ), Iceland ( Moreras-Marti et al, 2021 ), and volcanic provinces in New Zealand ( Power et al, 2018 ). In contrast, other studies have identified temperature as the most important driver of microbial community composition in hot springs ( Miller et al, 2009 ; Cole et al, 2013 ; Sharp et al, 2014 ; Podar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%